Effects of metronidazole on mesophilic and thermophilic fermentation: Biodegradation mechanisms, microbial communities, and reversibility. (October 2022) - Zhao, Wenqian; Zhang, Xiaodong; Cai, Yanpeng; Zhao, Shan; Wang, Shuguang
Graphical abstract: Highlights: Metronidazole was removed mainly by opening the imidazole ring for biodegradation. Metronidazole has a stronger inhibitory effect on mesophilic fermentation. Metronidazole specifically altered the microbial community structure. Thermophilic fermentation was more suitable for the removal of metronidazole. Abstract: Metronidazole (MNZ), an antibiotic that is specifically used for the treatment of anaerobic infections, may inhibit anaerobic fermentation. This work was designed to understand the fate and effects of MNZ in mesophilic fermentation (MF) and thermophilic fermentation (TF), respectively. The results showed that the removal of MNZ mainly occurred via biodegradation, rather than adsorption, and that MNZ could be completely degraded by opening the imidazole ring. MFs were more strongly inhibited by MNZ than TFs. MNZ concentration increased from 0 to 25 mg/L, hydrogen yield (HY) decreased from 167.5 to 16.8 mL/g glucose (90.0% decrease), and butyrate yield almost completely disappeared in MFs, whereas in TFs, HY decreased only from 101.1 to 89.3 mL/g glucose (11.7% decrease), and ethanol yield increased by 39.8%. Illumina MiSeq sequencing analysis showed that MNZ reduced the abundance of hydrogen-producing bacteria. Furthermore, the inhibition of MNZ on anaerobic fermentation was reversible.